Kontribusi Instrumen Perbankan Syariah terhadap Pertumbuhan Ekonomi Indonesia Tahun 2005-2021 - Mulyadi, Sandi; Suryanto, Asep (Jurnal Magister Ekonomi Syariah, 2022)
This research aims to analyze the role of Islamic banks in economic growth. The writing of this research is motivated by the rapid development of Islamic banking in Indonesia which needs to be balanced with its contribution to economic growth. This research is based on research questions about the development of Islamic banks in Indonesia, and the contribution of Islamic banks to Indonesia's economic growth before and during this pandemic, through third party financing, financing, and Islamic bank assets in the Indonesian economy. The method used in this study is quantitative by analyzing secondary data processed by Eviews 10 using the VECM method and using quarterly time series data from 2005 to 2021. The results of the study using the VECM method show that Islamic bank third party funds have a positive effect, total bank assets Sharia has a negative effect, and financing has no long-term or short-term effect on economic growth. Based on tests conducted by IRF, the movement of economic growth in response to the shock of these variables has been volatile for the next 60 years. This means that Islamic banks play an important role in Indonesia's economic growth. The proposed solution is for Islamic banks to increase market share, increase the proportion of funding from the Mudharabah and Musyarakah programs, tighten regulations, improve quality and quantity, and keep up with technological advances.